PENGARUH MODEL DISCOVERY LEARNING TERHADAP KEMAMPUAN GENERIK SAINS SISWA KELAS XI MAN ASAHAN PADA MATERI TERMOKIMIA - Talitha Azmi Siregar; Rudi Munzirwan Siregar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The purpose of this study is to investigate how using the Discovery Learning paradigm affects the general science abilities of eleventh-grade students studying thermochemistry at MAN Asahan. 34 students make up the sample size for this one-group pretest–posttest research design. Multiple-choice questions based on six measures of general science skills and observation sheets were used to collect data. Expertise have confirmed the research equipment, and the KR-20 dependability test yielded a very high criteria. Because the data did not have a normal distribution, N-Gain and the Wilcoxon test were used for data analysis. The average student score increased from 63.62 on the pretest to 85.29 on the posttest, according to the research findings, with an N-Gain value of 0.54 (medium criteria). The concept-building indicator was the most improved of all the generic science skill indicators. It is clear from the Wilcoxon test results that there is a significant difference (p < 0.05) between the pretest and posttest that the Discovery Learning model significantly affects students' general science skills and is highly successful in improving comprehension and scientific thinking abilities.